Embracing Otherness? A VR Body Hack by Morehshin Allahyari (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2024)
“Embracing the otherness” is a phrase that is borrowed from Morehshin Allahyari’s virtual reality artwork She Who Sees the Unknown: Kabous, the Right Witness, and the Left Witness (2019). In this article, I am using this phrase to question the figuration of self and other as staged by Allahyari in her work. By deploying an overwhelming effect of immersion specific to the technological features of VR, Allahyari establishes a physical as well as an emo- tional relationship to the other. But instead of encouraging a sense of closeness, which is likely to be connected to the idea of “embracing otherness” as well as to the vision of VR as “empathy machine,” this immersive experience has the opposite effect. I argue that it weirdly plays with the appropriative mechanisms of othering, unsettles the viewer’s sovereignty, and thus initiates a rather “strange encounter.” In this sense, I will examine Allahyari’s use of VR’s immersiveness as a “body hack” and elaborate how I read her artwork as a critical commentary on the debate of the transformative potential of VR as “empathy machine.”Cover caption: Morehshin Allahyari, She Who Sees the Unknown: Kabous, The Right Witness, and The Left Witness, snapshots from VR video, commissioned by The Shed, image courtesy of the artist, 2019.
Keywords: Otherness; Strange encounter; Empathy machine; Virtual reality; Uncanny